Glycerol mycolates from synthetic mycolic acids. (7th August 2017) - Ali, Omar T.; Sahb, Mohaned M.; Al Dulayymi, Juma'a R.; Baird, Mark S.
Abstract: R- and S-Glycerol mycolates derived from single synthetic α-, keto- and methoxy-mycolic acids are described. Graphical abstract: Abstract: R- and S-Glycerol mycolates derived from single synthetic α-, keto- and methoxy-mycolic acids, such as compound A are described. Highlights: R - and S -glycerol mycolates from synthetic mycolic acids. GroMM synthesis. Alpha-, keto- and methoxy-mycolic acids.